2013
DOI: 10.1002/ange.201309207
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Cp‐Rhodium(III)‐Catalyzed Asymmetric Hydroarylations of 1,1‐Disubstituted Alkenes

Abstract: Metal‐catalyzed functionalizations at the ortho position of a directing group have become an efficient bond‐forming strategy. A wide range of transformations that employ Cp*RhIII catalysts have been described, but despite their synthetic potential, enantioselective variants that use chiral versions of the Cp* ligand remain scarce (Cp*=pentamethyl cyclopentadienyl). Cyclopentadienyl compounds with an atropchiral biaryl backbone are shown to be suitable ligands for the efficient intramolecular enantioselective h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(12 citation statements)
references
References 73 publications
0
10
1
1
Order By: Relevance
“…[12] Based on this,t he NHC ligand L1, which exhibited high performance in the our previous study of copper catalysis,w as initially used in the reaction between benzothiazole (1a;1 .5 equiv) and the E-allylic phosphate (E)-2a in the presence of CuCl (10 mol %) and LiOtBu (2.2 equiv) in 1,4-dioxane at 25 8 8C ( Table 1, entry 1). In contrast to the results obtained using oxygen-functionalized NHC ligands,n or eaction occurred with either NHC ligands lacking an oxygen functional group, such as L5,I Mes,a nd SIMes,o rw ithout exogenous ligand (entries [6][7][8][9]. [13] To our delight, however, changing the phenol group of L1 to an aphthol group,togive the new ligand L2,caused marked increases in product yield (77 %) and enantioselectivity (68 %), with the exclusive regioselectivity unchanged (entry 2).…”
contrasting
confidence: 62%
See 3 more Smart Citations
“…[12] Based on this,t he NHC ligand L1, which exhibited high performance in the our previous study of copper catalysis,w as initially used in the reaction between benzothiazole (1a;1 .5 equiv) and the E-allylic phosphate (E)-2a in the presence of CuCl (10 mol %) and LiOtBu (2.2 equiv) in 1,4-dioxane at 25 8 8C ( Table 1, entry 1). In contrast to the results obtained using oxygen-functionalized NHC ligands,n or eaction occurred with either NHC ligands lacking an oxygen functional group, such as L5,I Mes,a nd SIMes,o rw ithout exogenous ligand (entries [6][7][8][9]. [13] To our delight, however, changing the phenol group of L1 to an aphthol group,togive the new ligand L2,caused marked increases in product yield (77 %) and enantioselectivity (68 %), with the exclusive regioselectivity unchanged (entry 2).…”
contrasting
confidence: 62%
“…Changing the hydroxy group of L3 to am ethoxy group was unfavorable for both product yield and branch regioselectivity,a lthough the reduction in enantioselectivity was not significant (entry 5). In contrast to the results obtained using oxygen-functionalized NHC ligands,n or eaction occurred with either NHC ligands lacking an oxygen functional group, such as L5,I Mes,a nd SIMes,o rw ithout exogenous ligand (entries [6][7][8][9]. Thus,f unctional roles were suggested for the OH and OMe groups in L3 and L4,respectively,asinthe case of copper-catalyzed enantioselective allylic alkylation of terminal alkynes.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…[48] Tuning the size of the R group on the biaryl backbone enabled an enantioselective hydroarylation of tethered alkenes, providing enantioenriched dihydrobenzofurans derivatives. For the hydroarylation reaction, it was revealed that the meta -alkoxy group was serving as a secondary directing group, thereby allowing activation of the more hindered ortho -C(sp 2 )–H bond.…”
Section: Rhodium Catalysismentioning
confidence: 99%